A Orientação Sexual na Revista Nova Escola - Adriana Candido da Silva; Leila Maria Ferreira Salles (Universidade Estadual Paulista Júlio de Mesquita Filho, 2007)
This study identifies and classifies articles about sexual education in Nova Escola magazine. The 118 numbers published from March of 1986 to December 1988 were analyzed. The survey shows that sexual education is frequently published issue, usually emphasizing rules, practices and patterns of behavior for teachers in classroom.